IL-5 in follicular fluid as a negative predictor of the intracytoplasmic sperm injection outcome. (January 2019) - Alhilali, Miaad Jabbar Sahib; Parham, Abbas; Attaranzadeh, Armin; Amirian, Malihe; Azizzadeh, Mohammad
Highlights: Elevated concentrations of IL-5 in FF is a moderate negative predictor for pregnancy in ICSI cycles. Higher IL-5 levels in FF were associated with poor oocyte quality. Elevated concentrations of IL-4 in FF were linked to good ICSI outcome. Higher GM-CSF in FF was associated with a decrease in mature oocytes. Abstract: Purpose: To determine the prognostic value of intrafollicular concentrations of some cytokines from women undergoing ovarian stimulation in the outcome of intracytoplasmic sperm injection/embryo transfer (ICSI/ET) cycles. Methods: A total of 80 patients were included in this study following ovarian stimulation and ICSI. Follicular fluids (FF) were collected at the day of oocyte retrieval. Ten cytokines including: tumor necrosis factor- alpha (TNF-α), interleukin (IL)-1β, IL-2, IL-4, IL-5, IL-6, CXCL8/IL-8, IL-10, granulocyte-macrophage colony stimulating factor (GM-CSF), and interferon gamma (IFN-γ) were measured using magnetic multiplex immunoassays. Results: Only the concentration of IL-5, IL-4, and GM-CSF in FF were significantly different (p < 0.05) between ICSI cycles that resulted in pregnancy and those that failed. Elevated FF IL-5 levels were associated with poor oocyte quality, which decreases the chance of both biochemical and clinical pregnancy. Higher FF GM-CSF associated with decrease of mature oocytes, while higher FF IL-4 concentrations were linked to good ICSI outcome through increased fertilization rate. Conclusions: The elevated intrafollicular concentrations of IL-5 seem to be a negative predictor to the pregnancy outcome in ICSI cycles.